(untitled) (Swiss Medical Weekly, 2023)
There is a great deal of empirical evidence that owning a firearm increases the risk of dying from suicide. Most suicides are impulsive. Nearly 50% of survivors of suicide attempts report that they took less than 10 minutes between the decision to die and their suicide attempt. The great majority of these suicide survivors never make another attempt and die of natural causes. Because nearly 90% of firearm suicide attempts have a deadly outcome, gun owners are unlikely to have such a second chance. These impulsive suicide attempts are typically carried out with the means at hand. Swiss men have much higher firearm suicide rates than men in other European countries and this excess is likely to be due to their easy access to guns, because army conscripts have to keep their guns at home. When the number of conscripts was nearly halved in 2003/4 as a result of the Swiss Army Reform XXI, the number of army-issued firearms was reduced by an estimated 20%. An analysis of suicide rates before and after the reform indicated that male (but not female) suicide rates decreased by 8%, with no evidence of substitution with other means of suicide. If the army would require that the remaining half of conscripts had to keep their weapons at their barracks rather than at home, a further decrease in male suicide rates could be expected.